Pendekatan Manajemen Kelas Berbasis Positif (Positive Classroom Management) (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
The positive classroom management approach has emerged in response to the need to create a more humanistic, constructive, and character oriented learning environment. In modern educational contexts, teachers are expected not only to facilitate student learning but also to establish a supportive and collaborative classroom atmosphere that encourages active student participation. This study aims to analyze the concepts, implementation strategies, impacts, and challenges of the positive classroom management approach through a Systematic Literature Review (SLR) of ten relevant scientific articles and journals. To identify the strategies employed, their influence on students motivation and learning outcomes, and the difficulties encountered in their implementation, the study was conducted by first selecting recent literature. The findings indicate that positive classroom management is generally implemented through consistent routines, the creation of a supportive learning environment, the use of reinforcement that promotes learning, and the adoption of collaborative learning models. This approach has been shown to enhance motivation, discipline, participation, independence, and students readiness to learn across various educational levels. However, its implementation still faces several challenges, including diverse student characteristics, limited resources, varying levels of teacher competence, and resistance to change. The results of this study underscore the importance of teacher training, school administration support, and consistent classroom management to ensure the effectiveness of positive management strategies. This review provides both theoretical and practical foundations for developing adaptive and character-oriented learning models.